Reasonableness and Law
XVII, 464 p.
Keywords: Reasonableness is at the centre of legal debate, both in academic circles and in practice. This unique reference work adopts an interdisciplinary perspective, merging jurisprudence, legal theory, political philosophy and the different branches of law. All aspects relating to reasonableness and law are addressed by the most prominent scholars in the field. In the first part of the book, the focus is on jurisprudential analyses of the concept of reasonableness and on its moral, political and constitutional implications. In the second part, reasonableness is examined in the different fields of law like Public, Private and International Law. Here in more detail the practical consequences of reasonableness are worked out, making this work of interest to practitioners as well as legal theorists.